Dry-process pre-lithiation silicon-based negative electrode with high first efficiency and preparation method of dry-process pre-lithiation silicon-based negative electrode

Through the dry prelithiation technology, the negative electrode active material and the prelithiation reagent are mixed at high speed, and the pressure is used to induce lithium and silicon to form an alloy, which solves the problem of lithium loss caused by volume expansion during the lithiation of silicon-based materials, and achieves a high-end Effectiveness, uniform prelithiation and improved conductivity.

CN119419214APending Publication Date: 2025-02-11ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1

Patent Information

Application Number
CN202411537792.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, the huge volume expansion of silicon-based materials during the lithiation process leads to damage to the passivation layer on the surface of the lithiated silicon, resulting in serious lithium loss and low initial Coulomb efficiency and cycling efficiency.

Method used

The dry prelithiation method is used to mix the negative electrode active material with the prelithiation reagent at a high speed, and the pressure generated during the mixing process is used to induce lithium and silicon to form a lithium-silicon alloy at the contact point to achieve uniform prelithiation.

Benefits of technology

High first-term efficiency and uniform pre-lithiation are achieved, which significantly enhances lithium/electronic conductivity, reduces volume expansion during lithium embedding, and improves the mechanical softness of the electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419214A_ABST
    Figure CN119419214A_ABST
Patent Text Reader

Abstract

The invention discloses a high-first-efficiency dry pre-lithiation silicon-based negative electrode and a preparation method thereof. Comprising the following steps: (1) mixing a negative electrode active material and a pre-lithiation reagent at a high speed to obtain a dry-process pre-lithiated silicon-based negative electrode material; and (2) mixing and fiberizing the pre-lithiated silicon-based negative electrode material, a binder and a conductive agent, pressing the fiberized material into a fiberized film through high-temperature rolling, and finally compounding the obtained fiberized film with a current collector through hot rolling to form the dry-method electrode plate. On one hand, the physical contact between a lithiation reagent and a silicon material can be adjusted in a high-speed mixing process in a dry pre-lithiation manner, and pre-lithiation is induced by utilizing the pressure generated by a contact point; and on the other hand, the pre-lithiation reagent is added in the material mixing process, so that the initial coulombic efficiency of the negative plate can be improved by compensating the loss of active lithium in the reaction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a high-initial-efficiency dry-process composite silicon-based negative electrode and a preparation method thereof. Background Art

[0002] The theoretical capacity of silicon (Si) is as high as 3579 mAh g -1 , volume capacity up to 2194Ah L -1 , compared with traditional graphite (372mAh g -1 ,719Ah L -1 ) is several times higher and is one of the most promising alternatives, which has been widely studied in academia and industry. However, a key challenge in the application of Si-based anodes is the huge volume expansion (~280%) during the lithiation process, which leads to the destruction of the passivation layer on the surface of lithiated silicon (i.e., solid electrolyte interface (SEI)), increased surface exposure, continuous consumption of electrolyte due to the newly formed SEI, particle crushing, and separation of materials from the current collector, resulting in severe lithium loss, causing the initial coulombic efficiency (ICE) and CE of Si-based materials during the cycle process to be much lower than that of graphite. Therefore, how to improve the ICE of Si-based materials has become a research hotspot for more and more people.

[0003] Pre-lithiation is an effective method to increase lithium-ion capacity and energy density. It can be achieved through electrochemical methods, physical contact and chemical methods. Electrochemical pre-lithiation is to form an electrochemical pathway between lithium foil, organic electrolyte and silicon anode, and insert lithium into silicon under the drive of electric field. However, electrochemical pre-lithiation requires additional lithium, electrolyte, disassembly and assembly, which is difficult to apply in large-scale production. It is currently mainly used in laboratories. Chemical pre-lithiation is to introduce active lithium compounds (such as organic lithium compounds, Li 3 N or lithium-manganese alloy), lithium is inserted into the silicon negative electrode through redox reaction. However, for silicon-based materials, the redox potential of most lithium-aromatic complexes is too high to drip lithium ions into silicon-based materials. In addition, problems such as the cost of organic lithium compounds and their solutions, and the handling of highly reactive chemicals still exist. Physical contact pre-lithiation is to insert lithium into silicon by directly contacting the silicon negative electrode with lithium foil or molten lithium metal under a certain pressure for a period of time. Although the direct contact method can achieve pre-lithiation by using both the self-discharge of metallic lithium foil and the self-discharge of powder, it is relatively simple and efficient, and suitable for industrial production. However, the uneven distribution of contact points between lithium and the electrode often leads to a reduction in the pre-lithiation effect.

[0004] Patent CN 112531161A disperses the negative electrode active material and metallic lithium in an organic solvent, performs a hydrothermal reaction, and obtains a pre-lithium negative electrode material. The sedimentation of the particles cannot be controlled during the hydrothermal process, resulting in uneven pre-lithiation. Patent CN117558894A mixes SiOx material and lithium source in an organic solvent, and then puts them into a CVD rotary furnace, and heats and keeps them warm in an argon atmosphere for a pre-lithiation reaction. Not only does it need to remove the extra organic solvent, but it also needs to be heated by argon in the CVD rotary furnace, and the equipment and process are complicated.

[0005] Therefore, how to prepare a silicon-based negative electrode with high initial efficiency, uniform pre-lithiation and low equipment requirements has become an urgent problem that technicians in this field need to solve. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a high-initial-efficiency dry pre-lithiation silicon-based negative electrode and a preparation method thereof, wherein the negative electrode active material and the pre-lithiation reagent are mixed at high speed to form a lithium-silicon alloy material, and the physical contact between the pre-lithiation reagent and the silicon material is adjusted by appropriate pressure generated during the mixing process, and the pressure generated at the contact point is used to induce pre-lithiation. Because pre-lithiation is achieved during high-speed mixing, the active material and the pre-lithiation reagent can be evenly mixed to generate a uniformly distributed lithium-silicon alloy material.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A high first-efficiency dry pre-lithiation silicon-based negative electrode, characterized by comprising a negative electrode active material, a pre-lithiation agent, a conductive agent and a fiberizable binder.

[0009] Furthermore, the negative electrode active material includes any one of pure silicon material, silicon-oxygen material, silicon-carbon material, silicon-oxygen-carbon material, or a combination of at least two of them.

[0010] Furthermore, the pre-lithiation reagent includes inert lithium powder, lithium halide, lithium sulfide or lithium hydroxide, and any one or a combination of at least two of the above materials that have been surface treated.

[0011] Furthermore, the conductive material includes any one of single-walled carbon nanotubes, multi-arm carbon nanotubes, conductive carbon black, carbon fiber or graphene, or a combination of at least two of them.

[0012] Furthermore, the fiberizable binder includes at least one of poly(vinylidene fluoride-hexafluoropropylene), polymethyl methacrylate, styrene-butadiene rubber, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, polyacrylonitrile, polyvinyl alcohol, polyacrylic acid, (methyl) polyacrylonitrile, modified polymethyl methacrylate, polyvinylidene fluoride copolymers, and polystyrene, or a mixture of two or more thereof.

[0013] The present invention also provides a method for preparing the high initial efficiency dry pre-lithiation silicon-based negative electrode, comprising the following steps:

[0014] (1) Preparation of dry pre-lithiation silicon-based material: mixing the negative electrode active material and the pre-lithiation reagent to obtain the dry pre-lithiation silicon-based material;

[0015] (2) mixing: mixing the dry pre-lithiation silicon-based material obtained in step (1) with a conductive agent and a fiberizable binder;

[0016] (3) Film forming: the material obtained in step (2) is rolled into a film by a roller press;

[0017] (4) Coating: The film obtained in step (3) is laminated onto the current collector by hot rolling to obtain a dry pre-lithiation silicon-based negative electrode sheet.

[0018] Furthermore, in step (1), the pre-lithiation agent accounts for 2wt%-6wt% of the negative electrode active material; the mixing device is a high-speed disperser, a double planetary high-speed mixer or a high-speed grinder, the rotation speed is 5000-10000rpm, and the mixing time is 5min-30min.

[0019] Furthermore, in step (2), the dry pre-lithiated silicon-based material is mixed with the conductive agent and the fiberizable binder in a mass ratio of 95.5:2:2.5, with a mixing speed of 600-1600 rpm, a mixing time of 10-60 min, and a mixing temperature of 30-90°C.

[0020] Furthermore, the film forming temperature in step (3) is controlled at 60-150° C. and the pressure is 0.5-5t.

[0021] Furthermore, the hot rolling temperature in step (4) is 110-150°C.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] (1) The pre-lithiation method provided by the present invention utilizes that the lithium diffusion at the contact point between the pre-lithiation reagent and silicon follows Fick's second law of diffusion. The electrons in the pre-lithiation reagent migrate to the silicon under the action of the electric field of the potential difference (~0.4vs Li / Li) between the lithium source and the silicon, and then the lithium ions are transferred to the silicon by charge balance, thereby achieving convenient and effective pre-lithiation.

[0024] (2) The present invention simply mixes the negative electrode active material and the pre-lithiation agent by a high-speed mixing method, and uses the pressure generated during the mixing process to induce lithium and silicon to form a lithium-silicon alloy at the contact point for pre-lithiation, thereby providing a convenient, low-cost and scalable pre-lithiation method. Since the pre-lithiation is carried out during the eddy current mixing process, the pre-lithiation agent can be evenly distributed on the surface of the negative electrode active material, achieving better interface contact and achieving the purpose of uniform pre-lithiation.

[0025] (3) The developed pre-lithiated silicon anode has significantly enhanced lithium / electron conductivity, reduced volume expansion during lithium insertion, and improved mechanical flexibility of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is an energy dispersive X-ray spectrum of the dry pre-lithiation silicon-based material of Example 1;

[0028] Figure 2 This is a picture of Example 1 after mixing;

[0029] Figure 3 This is a picture of Example 1 after rolling;

[0030] Figure 4 This is a picture of Example 1 after lamination;

[0031] Figure 5 This is the first coulombic efficiency curve of the assembled half-cell test of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0032] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or are obtained by practicing the present invention. It should be understood by those skilled in the art that the specific embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0033] The dry pre-lithiation method is not particularly limited in the embodiments of the present invention. Any similar pre-lithiation method can be used in the present application without violating the inventive concept of the present application. As an embodiment, the pre-lithiation method includes but is not limited to one or more of a high-speed grinder, a vacuum planetary mixer, a vacuum degassing machine, a conical screw mixer, and a vacuum high-speed agitator for pre-lithiation.

[0034] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0035] Example 1

[0036] A method for preparing a dry pre-lithiated silicon-based negative electrode with high initial efficiency has the following steps:

[0037] Step (1): In order to prepare a lithiated silicon negative electrode material, silicon oxide (SiOx) and stable lithium metal powder (SLMP) are mixed at a high speed, with SLMP accounting for 5% of Si weight, at a rotation speed of 9000 rpm, and mixed for 10 minutes to obtain a lithiated silicon negative electrode material.

[0038] Step (2): The lithiated silicon negative electrode material obtained in step 1 is mixed with polytetrafluoroethylene (PTFE) and carbon nanotubes (CNT) in a mass ratio of 95.5:2:2.5, with a mixing speed of 1000 rpm, a mixing time of 15 min, and a mixing temperature of 65° C. to obtain a fiberized material.

[0039] Step (3): The fiberized material obtained in step (2) is rolled by a horizontal roller press, the temperature is controlled at 85° C., the pressure is 2 tons, and it is rolled into a dry film.

[0040] Step (4): The membrane obtained in step (3) and the current collector are subjected to hot rolling coating at a coating temperature of 130° C. to obtain a dry pre-lithiated silicon-based negative electrode.

[0041] Example 2

[0042] The difference between Example 1 and Example 2 is that in step (1), SLMP accounts for 6% of the weight of SiOx.

[0043] Example 3

[0044] The difference between Example 3 and Example 2 is that in step (1), SLMP accounts for 3% of the weight of SiOx.

[0045] Example 4

[0046] The difference between Example 4 and Example 1 is that the rotation speed in step (1) is 8000 rpm.

[0047] Example 5

[0048] The difference between Example 5 and Example 1 is that the rotation speed in step (1) is 7000 rpm.

[0049] Example 6

[0050] The difference between Example 6 and Example 1 is that the rotation speed in step (1) is 6000 rpm.

[0051] Example 7

[0052] A method for preparing a dry pre-lithiated silicon-based negative electrode with high initial efficiency has the following steps:

[0053] Step (1): In order to prepare a lithiated silicon negative electrode material, silicon oxide (SiOx) and lithium hydroxide are mixed at a high speed, with the lithium hydroxide accounting for 5% of the weight of Si, at a rotation speed of 9000 rpm, and mixed for 10 minutes to obtain a lithium hydroxide lithiated silicon negative electrode material.

[0054] Step (2): The lithiated silicon negative electrode material obtained in step 1 is mixed with polytetrafluoroethylene (PTFE) and carbon nanotubes (CNT) in a mass ratio of 95.5:2:2.5, with a mixing speed of 800 rpm, a mixing time of 10 min, and a mixing temperature of 80° C. to obtain a fiberized material.

[0055] Step (3): The fiberized material obtained in step (2) is rolled by a horizontal roller press, the temperature is controlled at 90° C., the pressure is 2.6 tons, and it is rolled into a dry film.

[0056] Step (4): The membrane obtained in step (3) and the current collector are subjected to hot rolling coating at a coating temperature of 120° C. to obtain a dry pre-lithiated silicon-based negative electrode lithiated with lithium hydroxide.

[0057] Example 8

[0058] A method for preparing a dry pre-lithiated silicon-based negative electrode with high initial efficiency has the following steps:

[0059] Step (1): In order to prepare a lithiated silicon negative electrode material, silicon oxide (SiOx) and Li-S are mixed at a high speed, with Li-S accounting for 5% of the weight of Si, at a rotation speed of 9000 rpm, and mixed for 10 minutes to obtain a Li-S lithiated silicon negative electrode material.

[0060] Step (2): The lithiated silicon negative electrode material obtained in step 1 is mixed with polytetrafluoroethylene (PTFE) and carbon nanotubes (CNT) in a mass ratio of 95.5:2:2.5, with a mixing speed of 900 rpm, a mixing time of 12 min, and a mixing temperature of 85° C. to obtain a fiberized material.

[0061] Step (3): The fiberized material obtained in step (2) is rolled by a horizontal roller press, the temperature is controlled at 90° C., the pressure is 3 tons, and it is rolled into a dry film.

[0062] Step (4): The membrane obtained in step (3) and the current collector are subjected to hot rolling coating at a coating temperature of 1110° C. to obtain a dry pre-lithiation silicon-based negative electrode.

[0063] Example 9

[0064] A method for preparing a dry pre-lithiated silicon-based negative electrode with high initial efficiency has the following steps:

[0065] Step (1): To prepare a lithiated silicon negative electrode material, silicon oxide (SiOx) and Li 3 YC 6 High speed mixing, Li 3 YC 6 5% by weight of Si, the rotation speed is 9000rpm, and the mixing is carried out for 10 minutes to obtain Li 3 YC 6 Lithiated silicon anode material.

[0066] Step (2): The lithiated silicon negative electrode material obtained in step 1 is mixed with polyvinylidene fluoride (PVDF) and carbon nanotubes (CNT) in a mass ratio of 95.5:2:2.5, with a mixing speed of 1000 rpm, a mixing time of 15 min, and a mixing temperature of 65° C. to obtain a fiberized material.

[0067] Step (3): The fiberized material obtained in step (2) is rolled by a horizontal roller press, the temperature is controlled at 85°C, the pressure is 2t (write the specific point value), and calendered into a dry film.

[0068] Step (4): The membrane obtained in step (3) and the current collector are subjected to hot rolling coating at a coating temperature of 130° C. to obtain a dry pre-lithiated silicon-based negative electrode.

[0069] Example 10

[0070] A method for preparing a dry pre-lithiated silicon-based negative electrode with high initial efficiency has the following steps:

[0071] Step (1): To prepare a lithiated silicon negative electrode material, silicon oxide (SiOx) and Li 3 InCl 6 High speed mixing, Li 3 InCl 6 5% by weight of Si, the rotation speed is 9000rpm, and the mixing is carried out for 10 minutes to obtain Li 3 InCl 6 Lithiated silicon anode material.

[0072] Step (2): The lithiated silicon negative electrode material obtained in step 1 is mixed with polytetrafluoroethylene (PTFE) and conductive carbon black (SP) in a mass ratio of 95.5:2:2.5, with a mixing speed of 1000 rpm, a mixing time of 12 min, and a mixing temperature of 70° C. to obtain a fiberized material.

[0073] Step (3): The fiberized material obtained in step (2) is rolled by a horizontal roller press, the temperature is controlled at 90° C., the pressure is 2.7 tons, and it is rolled into a dry film.

[0074] Step (4): The membrane obtained in step (3) and the current collector are subjected to hot rolling coating at a coating temperature of 120° C. to obtain a dry pre-lithiation silicon-based negative electrode.

[0075] Comparative Example 1

[0076] The difference between Comparative Example 1 and Example 1 is that in step (1), SLMP accounts for 0% by weight of Si.

[0077] Comparative Example 2

[0078] The difference between Comparative Example 2 and Example 1 is that the rotation speed in step (1) is 5000 rpm.

[0079] Comparative Example 3

[0080] The difference between Comparative Example 3 and Example 1 is that the rotation speed in step (1) is 10000 rpm.

[0081] Comparative Example 4

[0082] This comparative example provides a wet pre-lithiation negative electrode material and a preparation method thereof, which is different from Example 1 in that in step (1), 5% of SLMP is dispersed in a xylene solution composed of poly(styrene-butadiene-co-butadiene) rubber (SBR) and polystyrene (PS); 20% of SiOx is dispersed in N-methylpyrrolidone (NMP), and then the SLMP dispersion is mixed with the SiOx dispersion, and vacuum dried to obtain a wet pre-lithiation negative electrode material. The remaining steps are the same as Example 1.

[0083] The negative electrode sheets prepared in Examples 1-10 and Comparative Examples 1-4 were tested, and the test steps were as follows:

[0084] Element characterization: Energy dispersive X-ray spectroscopy (EDS) was used to test the distribution of different elements on the dry pre-lithiation negative electrode material obtained in step (1) of Example 1.

[0085] First charge and discharge test: button half-cells were assembled using the dry pre-lithiation negative electrode materials obtained in Examples 1 to 10 and Comparative Examples 1 to 4 and lithium sheets, and the electrolyte was 1.5M LiPF 6 , EC:EMC=3:7. Then the obtained button cell was subjected to the first charge and discharge test at a test temperature of 30°C and a rate of 0.05C.

[0086] Table 1 shows the first charge specific capacity, first discharge specific capacity and first coulombic efficiency obtained by assembling half-cells of samples prepared in the embodiments and comparative examples:

[0087] Table 1

[0088]

[0089] As can be seen from Table 1, compared with Comparative Example 1, the first coulombic efficiency of Example 1 is greatly improved, and compared with the wet pre-lithiation of Comparative Example 4, it is also improved. As can be seen from Table 1, during dry pre-lithiation, the mixing speed has a greater impact on the first coulombic efficiency. When the speed is too low (Comparative Example 2), the pressure generated is insufficient, and less Li-Si alloy phase is formed at the interface of Li and SiOx, and the degree of lithiation is low, resulting in a decrease in the first coulombic efficiency. When the speed is too high (Comparative Example 3), the pressure generated is too large, causing overoxidation of SLMP, which also makes the degree of lithiation low, resulting in a decrease in the first coulombic efficiency.

[0090] The energy dispersive X-ray spectroscopy (EDS) test results of the pre-lithiation material obtained in Example 1 are as follows: Figure 1 As shown. Since the X-ray transition energy of Li is low, there is no EDS signal in the yellow dotted line area of ​​the sample after pre-lithiation, which can be classified as pure metallic lithium ( Figure 1 a). And from the EDS image, it can be seen that the sample after pre-lithiation has two types of structural domains: 1) composed of different Si and Li + The structural domains composed of Si and Li + The first domain shows the new chemical composition of the alloy formed by the precursor. + Sandwiched between Si, a different morphology is formed from the SLMP precursor powder. + No EDS signal was detected in the region of the second domain. The second domain presents a completely different morphology from the original SiOx and SLMP powders, more similar to charged (lithiated) Si, where the gaps between individual SiOx particles disappear and large SiOx blocks are formed. Moreover, EDS signals of Si can be detected in these regions ( Figure 1 b). In addition, it can be seen from the EDS image that a uniform Li-Si alloy phase is formed on the surface of Si. The above results show that after SLMP and SiOx are mixed at high speed, a uniform Li-Si alloy phase is formed at the interface between Li and Si, proving that SLMP can perform dry pre-lithiation on SiOx.

[0091] Figure 2 This is a picture of the fiberization after mixing in Example 1. From the picture, it can be clearly seen that the fiberized silk threads wrapped on the surface of the active substance are successful.

[0092] Figure 3This is a photo of Example 1 after rolling. The results show that the electrode has good continuous film forming properties after rolling, with a smooth surface, uniform thickness, and no holes, indicating that dry pre-lithiation will not affect the quality of the film.

[0093] Figure 4 This is a photo of Example 1 after coating. It can be seen from the picture that the prepared membrane is tightly attached to the current collector without bulging or warping.

[0094] Figure 5 From the first coulombic efficiency curve obtained by the test in Example 1, it can be seen that in the curve without pre-lithiation, the voltage platform during the first charge appears between 0.2-0.3V, which is the irreversible capacity loss caused by SiOx breakage. After pre-lithiation, it was observed that the voltage platform was significantly reduced, which indicates that the pre-lithiation active material and residual lithium can compensate for the loss of active lithium. It can be seen from the figure that the reversible capacity of the pre-lithiation material is also increased from 66.13% to 99.89% compared with the first coulombic efficiency of the material without pre-lithiation (Comparative Example 1).

[0095] In summary, in the present invention, the dry pre-lithiation can provide a lithium source not only in the first cycle, but also in the long-term cycle, thereby helping to improve ICE. In addition, the dry process can make the lithium metal powder evenly distributed among the active materials, so that the lithium ions can easily spread throughout the active material, thereby achieving uniform pre-lithiation of the electrode.

[0096] The pre-lithiation method provided by the present invention utilizes the lithium diffusion at the contact point between the pre-lithiation reagent and silicon to follow Fick's second law of diffusion. The electrons in the pre-lithiation reagent migrate to the silicon under the action of the electric field of the potential difference (~0.4vs Li / Li) between the lithium source and the silicon, and then the lithium ions are transferred to the silicon by charge balance, thereby realizing convenient and effective pre-lithiation. The present invention uses the pressure generated during the mixing process to induce lithium and silicon to form a lithium-silicon alloy at the contact point for pre-lithiation by mixing the negative electrode active material and the pre-lithiation reagent at high speed, thereby providing a convenient, low-cost and scalable pre-lithiation method. On the one hand, since the pre-lithiation is carried out during the high-speed mixing process, the pre-lithiation reagent can be evenly distributed on the surface of the negative electrode active material, achieving better interface contact and achieving the purpose of uniform pre-lithiation; on the other hand, the developed pre-lithiation silicon negative electrode has significantly enhanced lithium / electron conductivity, reduced volume expansion during lithium insertion, and improved mechanical flexibility of the pole piece. Therefore, it is very important to use appropriate pressure to improve the physical contact between lithium ions and silicon raw materials and achieve a favorable pressure-induced pre-lithiation effect.

[0097] The above embodiments of the present invention are for inspiration. Through the above description, relevant technicians can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A dry pre-lithiation silicon-based negative electrode with high initial efficiency, characterized in that: The invention comprises a negative electrode active material, a pre-lithiation agent, a conductive agent and a fiberizable binder.

2. The high initial efficiency dry pre-lithiation silicon-based negative electrode according to claim 1, characterized in that: The negative electrode active material includes any one of pure silicon material, silicon-oxygen material, silicon-carbon material, and silicon-oxygen-carbon material, or a combination of at least two of them.

3. The high first-efficiency dry pre-lithiation silicon-based negative electrode according to claim 1, characterized in that: The pre-lithiation reagent includes inert lithium powder, lithium halide, lithium sulfide or lithium hydroxide, and any one or a combination of at least two of the above materials after surface treatment.

4. The high initial efficiency dry pre-lithiation silicon-based negative electrode according to claim 1, characterized in that: The conductive material includes any one of single-walled carbon nanotubes, multi-arm carbon nanotubes, conductive carbon black, carbon fiber or graphene, or a combination of at least two of them.

5. The high first-efficiency dry pre-lithiation silicon-based negative electrode according to claim 1, characterized in that: The fiberizable binder includes at least one of poly(vinylidene fluoride-hexafluoropropylene), polymethyl methacrylate, styrene-butadiene rubber, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, polyacrylonitrile, polyvinyl alcohol, polyacrylic acid, (methyl) polyacrylonitrile, modified polymethyl methacrylate, polyvinylidene fluoride copolymers, and polystyrene, or a mixture of two or more thereof.

6. The method for preparing a dry pre-lithiated silicon-based negative electrode with high initial efficiency according to claim 1, characterized in that: The following steps are involved: (1) Preparation of dry pre-lithiation silicon-based materials: mixing the negative electrode active material and the pre-lithiation reagent to obtain the dry pre-lithiation silicon-based material; (2) Mixing: mixing the dry pre-lithiation silicon-based material obtained in step (1) with a conductive agent and a fiberizable binder; (3) Film formation: the material obtained in step (2) is rolled into a film by a roller press; (4) Coating: The film obtained in step (3) is laminated onto the current collector by hot rolling to obtain a dry pre-lithiation silicon-based negative electrode sheet.

7. The method for preparing a dry pre-lithiated silicon-based negative electrode according to claim 1, characterized in that: In step (1), the pre-lithiation agent accounts for 2wt%-6wt% of the negative electrode active material; the mixing device used is a high-speed disperser, a double planetary high-speed mixer or a high-speed grinder, the rotation speed is 5000-10000rpm, and the mixing time is 5min-30min.

8. The method for preparing a dry pre-lithiated silicon-based negative electrode according to claim 1, characterized in that: In the step (2), the dry pre-lithiated silicon-based material is mixed with the conductive agent and the fiberizable binder in a mass ratio of 95.5:2:2.5, the mixing speed is 600-1600 rpm, the mixing time is 10-60 min, and the mixing temperature is 30-90°C.

9. The method for preparing a dry pre-lithiated silicon-based negative electrode according to claim 1, characterized in that: The film forming temperature in step (3) is controlled at 60-150°C and the pressure is 0.5-5t.

10. The method for preparing a dry pre-lithiated silicon-based negative electrode according to claim 1, characterized in that: The hot rolling temperature in step (4) is 110-150°C.

Citation Information

Patent Citations

  • Pre-lithium negative electrode material, preparation method thereof, pre-lithium negative electrode and pre-lithium battery

    CN112531161A

  • Preparation method and application of simple pre-lithiated nano-microstructure silicon-oxygen-carbon composite material

    CN117558894A

Cited By

  • Method for improving direct lithiation efficiency

    CN121583877A

  • A dry pre-lithiation solid negative electrode sheet and a preparation method and application thereof

    CN122950391A